Entrepreneurial and Market Orientation on Coffee Shops Performance Mediated By Competitive Advantage - Amelia Veronica; Alfonsius (Business Review and Case Studies, 2026)
Background: The growth of coffee culture has changed coffee shops into lifestyle and social spaces, leading to the rapid growth of coffee shops in Medan. This rapid expansion has created a competitive environment where many coffee shops face challenges in sustaining business performance, with sales declining and even shutting down recently.Purpose: This study aims to examine the influence of entrepreneurial orientation and market orientation on the business performance of coffee shops in Medan, with competitive advantage as a mediating variable.Design/methodology/approach: A quantitative approach was used, with data collected through Google Forms from 100 coffee shop entrepreneurs in Medan using purposive sampling and analyzed using PLS-SEM.Findings/Results: The results indicate that entrepreneurial orientation and competitive advantage significantly influence business performance, while market orientation does not significantly influence business performance. Competitive advantage mediates the relationship between entrepreneurial and market orientation on business performance.Conclusion: Competitive advantage serves as a key mechanism through which entrepreneurial and market orientations influence business performance.Originality/value (State of the art): This study introduces a structured framework by exploring the mediating role of competitive advantage in the relationship between entrepreneurial orientation, market orientation, and business performanceKeywords: business performance, coffee shops, competitive advantage, entrepreneurial orientation, market orientation